Annual phytoplankton succession results from niche-environment interaction. (22nd December 2020) - Caracciolo, Mariarita; Beaugrand, Grégory; Hélaouët, Pierre; Gevaert, Francois; Edwards, Martin; Lizon, Fabrice; Kléparski, Loïck; Goberville, Eric
Abstract: Annual plankton succession has been investigated for many decades with hypotheses ranging from abiotic to biotic mechanisms being proposed to explain these recurrent patterns. Here, using data collected by the Continuous Plankton Recorder (CPR) survey and models originating from the MacroEcological Theory on the Arrangement of Life, we investigate Annual Phytoplankton Succession (APS) in the North Sea at a species level. Our results show that this phenomenon can be predicted well by models combining photosynthetically active radiation, temperature and macro-nutrients. Our findings suggest that APS originates from the interaction between species' ecological niches and the annual environmental fluctuations at a community level. We discuss our results in the context of traditional hypotheses formulated to explain this recurrent pattern in the marine field.